2021
DOI: 10.1038/s41419-021-04434-9
|View full text |Cite
|
Sign up to set email alerts
|

FDI-6 inhibits the expression and function of FOXM1 to sensitize BRCA-proficient triple-negative breast cancer cells to Olaparib by regulating cell cycle progression and DNA damage repair

Abstract: Inducing homologous-recombination (HR) deficiency is an effective strategy to broaden the indications of PARP inhibitors in the treatment of triple-negative breast cancer (TNBC). Herein, we find that repression of the oncogenic transcription factor FOXM1 using FOXM1 shRNA or FOXM1 inhibitor FDI-6 can sensitize BRCA-proficient TNBC to PARP inhibitor Olaparib in vitro and in vivo. Mechanistic studies show that Olaparib causes adaptive resistance by arresting the cell cycle at S and G2/M phases for HR repair, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…It has been implicated in several cancer subtypes, including RCC, and is highly prognostic [ 36 ]. Loss of FOXM1 has been shown to lead to mitotic decline, senescence, and necrosis in both aging and in cancer treatment with FDI-6 [ 54 , 55 ]. FDI-6 has been shown to cause nuclear fragmentation and subsequent dissolution in cancer cells [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been implicated in several cancer subtypes, including RCC, and is highly prognostic [ 36 ]. Loss of FOXM1 has been shown to lead to mitotic decline, senescence, and necrosis in both aging and in cancer treatment with FDI-6 [ 54 , 55 ]. FDI-6 has been shown to cause nuclear fragmentation and subsequent dissolution in cancer cells [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of FOXM1 has been shown to lead to mitotic decline, senescence, and necrosis in both aging and in cancer treatment with FDI-6 [ 54 , 55 ]. FDI-6 has been shown to cause nuclear fragmentation and subsequent dissolution in cancer cells [ 55 ]. We report this effect occurring in an immortal cell line, as well as in primary tumor cells lines.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, the ability of FOXM1 inhibition to target OCSC would be particularly relevant in the maintenance therapy setting, which aims at preventing or delaying OCSC-driven tumor recurrence once the bulk of the tumor has been removed by surgery and cytotoxic treatments. PARP inhibitors (PARPi) are commonly used as maintenance therapy in HGSOC patients with homologous recombination defects [26][27][28] ; since in other cancer types FOXM1 inhibitors synergized with this class of drugs 29,30 , we decided to investigate the effect of co-inhibiting PARP and FOXM1 in OCSC cocultured with the TME. TYK-nu/RFP sphere-derived cells were treated for 6 days with different doses of the PARPi Olaparib and Thiostrepton, alone or in combination.…”
Section: Parp Inhibitorsmentioning
confidence: 99%
“…Recent clinical trials showed that PARP inhibitor monotherapy served as second-line treatment for advanced urothelial cancer (UC) or as rst-line maintenance, and no signi cant e cacy advantage was observed in HRR-de cient patient population compared with the control group (14)(15)(16). Previous research has shown that Olaparib can cause HRR-pro cient cancer cells to arrest in S phase and G2/M phase, up-regulate various HRR proteins, and then activate HRR to repair DNA damage (17)(18), in which multiple cyclin proteins may also be involved as a reactive substrate, especially Cyclin D1(CCND1) which drives the transition of cell cycle from G1 phase to S phase, binding to BRCA2 protein to promote HRR (19)(20)(21).However, it is unknown whether inhibition of the cell cycle changes caused by Olaparib may interfere with HRR and enhance DNA damage.…”
Section: Introductionmentioning
confidence: 99%